Evaluation of Internal Audit Implementation: A Case Study at the Papua Province Inspectorate Office - Aedah, Nur; Sanggenapa, Isak (Technium Social Sciences Journal, 2021)
This study aims to discuss the evaluation of the implementation of internal audit with a case study at the Papua Province Inspectorate Office. This research is a type of quantitative research with a case study approach. The focus of this research is the evaluation of the implementation of internal audit based on the Regulation of the Minister of State for Administrative Reform Number: Per/05/M.Pan/03/2008 concerning Audit Standards for Government Internal Supervisory Apparatus in Standards for the Implementation of Performance Audits at the Provincial Inspectorate. The primary data in this study were obtained from questionnaires distributed to respondents at the Papua Province inspectorate. The results showed that the analysis of the implementation of the internal audit at the Provincial Inspectorate in Papua as a whole had effectively carried out its role. In the implementation of the internal audit the Papua Province inspectorate team had planned well. In the implementation of the internal audit, it is known that the audit supervision at the Papua provincial inspectorate has been running well and effectively. In the implementation of the internal audit, it was found that the Papua Province inspectorate team had carried out the procedures for collecting audit evidence well.